Mechanical behavior of coal under different mining rates: A case study from laboratory experiments to field testing - Gao, Mingzhong; Xie, Jing; Gao, Yanan; Wang, Wenyong; Li, Cong; Yang, Bengao; Liu, Junjun; Xie, Heping (International journal of mining science and technology, 2021)
During deep mining, the excavation disturbance stress path is the domination factor for the stability of the surrounding rock mass as well as the ground pressure. One of the important parameters of the stress path is the loading or unloading rate of the disturbed rock or coal, which depended on the mining rate. To achieve a well understanding of the mining rate and its effect on the coal behavior, a preliminary case investigation of the mechanical properties of the coal at the various mining rates in both the laboratory scale and field scale was performed. Based on the uniaxial compression test and the digital image correlation (DIC) method, the mechanical behavior of the coal samples, such as the evolution of the strength, surface deformation, crack propagation, and elastic strain energy of the coal under the various loading rates were analyzed. A threshold range of the loading rate has been observed. The uniaxial compressive strength (UCS) and releasable elastic strain energy (Ue) increase with increasing loading rate when the loading rate is below the threshold. Otherwise, the UCS and Ue may decrease with the loading rate. Under the low loading rate (≤0.05 mm/min), the tensile deformation of the original defects could result in crack coalescence, whereas failure of the coal matrix is the key contributor to the crack coalescence under the high loading rate (greater than0.05 mm/min). Afterwards, with the consideration of the bearing capacity (UCS) and energy release of the mining-disturbed coal mass (Ue), a power exponential relationship between the mining rate (MR) in the field and the critical loading rate (vc) in the laboratory was proposed. The application potential of the formulas was then validated against the field monitored data. Finally, based on the critical loading rate, the released strain energy, and the monitored pressure on the roof supports, a reasonable mining rate MR for the Ji15-31030 working face was determined to be approximately 3 m/d.